Critical insights for a sustainability framework to address integrated community water services: Technical metrics and approaches. (15th June 2015) - Xue, Xiaobo; Schoen, Mary E.; Ma, Xin (Cissy); Hawkins, Troy R.; Ashbolt, Nicholas J.; Cashdollar, Jennifer; Garland, Jay
Abstract: Planning for sustainable community water systems requires a comprehensive understanding and assessment of the integrated source-drinking-wastewater systems over their life-cycles. Although traditional life cycle assessment and similar tools (e.g. footprints and emergy) have been applied to elements of these water services (i.e. water resources, drinking water, stormwater or wastewater treatment alone), we argue for the importance of developing and combining the system-based tools and metrics in order to holistically evaluate the complete water service system based on the concept of integrated resource management. We analyzed the strengths and weaknesses of key system-based tools and metrics, and discuss future directions to identify more sustainable municipal water services. Such efforts may include the need for novel metrics that address system adaptability to future changes and infrastructure robustness. Caution is also necessary when coupling fundamentally different tools so to avoid misunderstanding and consequently misleading decision-making. Highlights: Few sustainability analyses consider the entire community water and sanitation system. Few sustainability analyses consider alternative water systems. Individual sustainability metrics have been applied separately for specific systems. Future research was discussed to improve the existing metrics and approaches. Demonstrating system analysis of water systems with real case studies is critical.